THE ROLE OF THE GOLD MICROELEMENT IN THE HUMAN ORGANISM (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the biological role of gold, one of the least studied yet vital trace elements in the human body. The participation of gold in maintaining homeostasis, stimulating immune system activity, and its importance in the treatment of joint and neurological diseases are discussed from a scientific perspective. The article also addresses the mechanisms of action of gold compounds at the cellular level.